2004
DOI: 10.1088/1126-6708/2004/12/051
|View full text |Cite
|
Sign up to set email alerts
|

QCD Green functions in a gluon field

Abstract: We formulate a dressed perturbative expansion of QCD, where the standard diagrams are evaluated in the presence of a constant external gluon field whose magnitude is gaussian distributed. The approach is Poincaré and gauge invariant, and modifies the usual results for hard processes only by power suppressed contributions. Long distance propagation of quarks and gluons turns out to be inhibited due to a branch point singularity instead of a pole at p 2 = 0 in the quark and gluon propagators. The dressing keeps … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 15 publications
(19 reference statements)
4
18
0
Order By: Relevance
“…In [2] for gluons in background configurations with, in general, non-zero field tensor and evaluated at leading order in N c −1 no residue of freely propagating bosons is found. Already for fundamental reasons this cannot be due to the specific form of the weight.…”
Section: Euclidean Spacementioning
confidence: 91%
See 3 more Smart Citations
“…In [2] for gluons in background configurations with, in general, non-zero field tensor and evaluated at leading order in N c −1 no residue of freely propagating bosons is found. Already for fundamental reasons this cannot be due to the specific form of the weight.…”
Section: Euclidean Spacementioning
confidence: 91%
“…Nevertheless, the different Lorentz components of a homogeneous pure gauge background commute. The background is to transform homogeneously under gauge transformations U [2]:…”
Section: Non-abelianmentioning
confidence: 99%
See 2 more Smart Citations
“…(2.9) below). In [3,4] we showed that the modification (1.3) can be obtained by assuming a constant background field and averaging over all components of this field with a gaussian weight. It was possible to calculate exactly the dressed quark and gluon propagators in the limit of a large number of colors (N c → ∞), i.e., for all planar Feynman diagrams.…”
Section: Introductionmentioning
confidence: 99%